2021
DOI: 10.1080/13696998.2021.1908000
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of the cell-based quadrivalent versus the standard egg-based quadrivalent influenza vaccine in Germany

Abstract: Background: Standard influenza vaccines are produced using egg-based manufacturing methods. Through the process, the resulting egg-adapted viral strains may differ from the selected vaccine strain. Cell-derived influenza vaccine manufacturing prevents egg-adaptation of the antigen which can improve vaccine effectiveness. We evaluated the cost-effectiveness of quadrivalent cell-derived influenza vaccine (QIVc) versus an egg-based quadrivalent influenza vaccine (QIVe) in preventing seasonal influenza from German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 25 publications
(39 reference statements)
1
33
0
1
Order By: Relevance
“…In addition, this assumption has a limited impact on our results since (1) we consider the observed influenza strain distribution, and (2) we have analyzed situations when the number of mismatched years was varied from one to five years and reached qualitatively similar results. In addition, our results are consistent with previous health-economic analyses of QIVc in Europe (UK, Spain, Italy, Germany) [29][30][31], where QIVc has been shown to be either cost-saving or highly cost-effective.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, this assumption has a limited impact on our results since (1) we consider the observed influenza strain distribution, and (2) we have analyzed situations when the number of mismatched years was varied from one to five years and reached qualitatively similar results. In addition, our results are consistent with previous health-economic analyses of QIVc in Europe (UK, Spain, Italy, Germany) [29][30][31], where QIVc has been shown to be either cost-saving or highly cost-effective.…”
Section: Discussionsupporting
confidence: 91%
“…Influenza infections in children and adults <65 years of age account for an estimated annual average economic burden of $1.84 billion in direct medical expenditures and $6.94 billion in indirect costs due to missed school by sick children and missed work by sick adults and the parents and guardians who care for children with influenza [54,55]. The results discussed in this review are part of a broader set of studies that have evaluated the relative vaccine effectiveness and cost effectiveness of IIV4c compared to IIV4e [27,[56][57][58][59]. The use of RWE to assess rVE will remain an important source of data for the timely assessment of current and future seasons.…”
Section: Discussionmentioning
confidence: 99%
“…We found that vaccination with QIVc would reduce the number of seasonal influenza cases, complications, hospitalizations, and deaths compared to QIVe. Endorsing this evidence, several studies evaluated the cost-effectiveness of QIVc compared to QIVe worldwide and demonstrated similar findings [ 17 , 18 , 19 , 21 ]. This result can be attributed to the fact that cell-based influenza vaccines can be more effective than traditional egg-based influenza vaccines, favoring several populations and clinical and economic outcomes [ 17 ].…”
Section: Discussionmentioning
confidence: 75%
“…The cost-effectiveness of QIVc has been reported for the United States (US) [ 16 , 17 ], Spain [ 18 ], Brazil [ 19 ], the United Kingdom (UK) [ 20 ], and Germany [ 21 ]. In the UK, Kohli et al reported the cost-effectiveness of extending QIVc vaccination regimen from at-risk to low-risk adults between 50 and 64 years of age [ 20 ].…”
Section: Introductionmentioning
confidence: 99%